Development and in vitro evaluation of coated pellets containing chitosan to potential colonic drug delivery - Ferrari, Priscileila Colerato [UNESP]; Souza, Fagner Magalhães; Giorgetti, Leandro; Oliveira, Giselle Faria [UNESP]; Ferraz, Humberto Gomes; Chaud, Marco Vinícius; Evangelista, Raul Cesar [UNESP] (Elsevier, 2013)
In this work pellets containing chitosan for colonic drug delivery were developed. The influence of the polysaccharide in the pellets was evaluated by swelling, drug dissolution and intestinal permeation studies. Drug-loaded pellets containing chitosan as swellable polymer were coated with an inner layer of Kollicoat® SR 30 D and an outer layer of the enteric polymer Kollicoat® MAE 30 DP in a fluidized-bed apparatus. Metronidazole released from pellets was assessed using Bio-Dis dissolution method. Swelling, drug release and intestinal permeation were dependent on the chitosan and the coating composition. The drug release data fitted well with the Weibull equation, indicating that the drug release was controlled by diffusion, polymer relaxation and erosion occurring simultaneously. The film coating was found to be the main factor controlling the drug release and the chitosan controlling the drug intestinal permeation. Coated pellets containing chitosan show great potential as a system for drug delivery to the colon. © 2012 Elsevier Ltd.
Keywords: Chitosan; Colonic drug delivery; Enteric coating; Intestinal permeation; Metronidazole; Pellets; Coating compositions; Dissolution methods; Drug dissolution; Drug release; Enteric polymer; Enteric-coating; Film coatings; In-vitro evaluation; Inner layer; Kollicoat; Outer layer; Polymer relaxations; Swellable polymers; Weibull; Drug delivery; Drug products; Fluidized beds; Ore pellets; Pelletizing; Plastic coatings; Polymers; Protective coatings; chitosan; drug carrier; metronidazole; polyvinyl acetate; polyvinyl derivative; animal; chemistry; colon; intestine absorption; kinetics; male; metabolism; permeability; rat; Wistar rat; Animals; Colon; Drug Carriers; Intestinal Absorption; Kinetics; Male; Permeability; Polyvinyls; Rats; Rats, Wistar